2019
DOI: 10.1088/1361-6463/ab45ce
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modelling of ceramic nanoparticle interactions and their influence on the thermal conductivity of nanofluids

Abstract: This is a repository copy of Multiscale modelling of ceramic nanoparticle interactions and their influence on the thermal conductivity of nanofluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…However, with the increase in concentration mean free path decrease. This suggested that with an increase in the concentration the reduction in mean free path could reduce the thermal transport as compared to the low concentration 53 . Similarly in another study, a critical concentration (0.0011 vol%) of MWCNTs has been reported where maximum thermal conductivity enhancement was observed.…”
Section: Resultsmentioning
confidence: 63%
See 4 more Smart Citations
“…However, with the increase in concentration mean free path decrease. This suggested that with an increase in the concentration the reduction in mean free path could reduce the thermal transport as compared to the low concentration 53 . Similarly in another study, a critical concentration (0.0011 vol%) of MWCNTs has been reported where maximum thermal conductivity enhancement was observed.…”
Section: Resultsmentioning
confidence: 63%
“…This suggested that with an increase in the concentration the reduction in mean free path could reduce the thermal transport as compared to the low concentration. 53 Similarly in another study, a critical concentration (0.0011 vol %) of MWCNTs has been reported where maximum thermal conductivity enhancement was observed. Beyond 0.0011%, a reduction in thermal conductivity was also noted up to certain limit of concentration.…”
Section: Thermal Conductivity Of Nfsmentioning
confidence: 62%
See 3 more Smart Citations